NTU: introdução ao pensamento filosófico bantu - Cunha Júnior, Henrique Antunes (2010)
This paper presents an introduction on cultural and thinking of Bantu societies. It refers to basics concepts of African philosophy. Works with the classificatory terms of Bantu languages as a part of collective philosophy gave by the Bantu social education. It is treated the significations of the classificatory terms Muntu, Kintu, Hantu, Kuntu and Nammo. It is also presented the geographical localization and general aspects of the Bantu society to possibilitya better understanding of the philosophical aspects.